(3cJGH SdhI GdMQja HefGXQI GdQHjY hGdNQja (B/s - (3GdLGMX, YeQh Hf HMQ Hf eMHhH,s 163-255 (3gLQjs ((3GdbGgQI (B:s (3TQcI fhGHZ GdacQ ddfTQ hGdJhRjY hGdJUOjQ,s, 2011)
(3jYO cJGH (B"(3SdhI GdMQja HefGXQI GdQHjY hGdNQja(B" (3ddeDda GdLGMX ef Cge GdcJH GdJj JfGhdJ afhf GdNWGHI hGdefGXQI aj GdCOH GdYQHj(B. (3jJVef gPG GdcJGH eLehYI ef GdefGXQGJ GdJj OGQJ Hjf TNUjGJ eNJdaI, MjK jbhe GdeDda HJUhjQ gPg GdefGXQGJ HCSdhH SGNQ hPcj, eSJNOeG aj Pdc eLehYI ef GdCSGdjH hGdJbfjGJ GdCOHjI GdeNJdaI(B. (3hjYO gPG GdcJGH ef Cge GdcJH GdJj JfGhdJ af GdefGXQI aj GdCOH GdYQHj, MjK jbOe GdeDda ef NdGdg OQGSI TGedI dgPG Gdaf, hjQUO ajg CSGdjH GdefGXQI hBOGHgG hCSGdjH GSJNOGe GdCOdI hGdHQGgjf ajgG(B. (3hbO GTJgQ GdeDda HCSdhHg GdSGNQ hGdPcj aj cJGHI gPG GdcJGH, MjK jbhe HJUhjQ GdefGXQGJ HCSdhH jLeY Hjf GdacGgI hGdMceI, eeG LYd gPG GdcJGH jMXi HTYHjI cHjQI aj GdCOH GdYQHj(B. (3hjecf Gdbhd Ef gPG GdcJGH jYO ef Cge GdcJH GdJj JfGhdJ af GdefGXQI aj GdCOH GdYQHj, MjK jbOe GdeDda ef NdGdg OQGSI TGedI dgPG Gdaf, hjQUO ajg CSGdjH GdefGXQI hBOGHgG hCSGdjH GSJNOGe GdCOdI hGdHQGgjf ajgG(B.s
Keywords: (3GdCOH GdYQHjs -- (3GdYUQ GdYHGSj GdKGfjs -- (3eLehYGJs